The Strategies for Promoting Tongging Tourism Village Through Social Media in Support of Sustainable Tourism - Amelia Meisy Sidauruk; Ikhlas Ramadhan; Triana Putri; Muhammad Rizki Lubis; Maharani Situmorang (The Postgraduate School of Tourism Sahid Polytechnic, 2026)
This study examines the promotional strategies of Tongging Tourism Village through social media as an effort to support sustainable tourism development. This study uses a participatory action approach methodology by directly conducting field studies and comprehensively reviewing the promotional strategies of Tongging Tourism Village through social media in the context of sustainable tourism development to explore the marketing position and promotional practices implemented by village managers, particularly through Instagram and digital platforms. Data were collected through in-depth interviews, documentation, and literature review. The participatory action approach was chosen because it is able to produce a comprehensive understanding that can be directly seen and felt by the author about the objects, phenomena, and social contexts studied, where the authors describe their findings systematically through narrative presentations. The findings reveal that the promotional activities align with two main strategies in the Ansoff Matrix, namely market penetration through the reactivation of the @desawisatatongging Instagram account, consistent reels publication, and collaboration with local tourism managers and market development, realized through the creation of an integrated village website, English-subtitled content, and information boards equipped with QR codes. These strategies resulted in a significant increase in digital visibility, indicated by the rise in average reel views from 1,702 to 3,902, with one reel reaching 9,558 views. The integration of the Marketing Mix (4P) further strengthened promotional effectiveness by enhancing information accessibility, price transparency, and destination image. Overall, the study concludes that social media-based promotion effectively supports sustainable tourism by improving information digitization, empowering local stakeholders, and expanding market reach. Recommendations are provided for tourism managers, local governments, and future research to enhance digital marketing and long-term sustainable tourism development.